PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN BERBASIS 4C PADA KELAS V SEKOLAH DASAR - Asteria Astri; Siti Halidjah; Dioty Auliya Vilda Gasya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to develop RPP product theme 2 (clean air for health) subtheme 3 (Maintaining the health of human respiratory organs) class V based on 4C (Critical Thinking and Problem Solving, Communication, Collaboration, Creativity and Innovation). The research method used is research and development (RnD) by adapting the Thiagarajan 4D design development model (Define, Design, Develop, Disseminate). This research only reached the Depelop stage, due to time constraints and the limitations of researchers. The data sources of this research are the results of the validation of two validators, and the results of the homeroom teacher's responses for VA and VB SDS Brother Nusa Indah, South Pontianak. The research instruments were interview guidelines, validation questionnaires, and teacher response questionnaires. The feasibility level of the RPP is based on the results of the validator team's assessment. The results showed 1) The feasibility of the 4C-based lesson plans (Critical Thinking and Problem Solving, Communication, Collaboration, Creativity and Innovation) was declared "very feasible" with an average score of 3.34. 2) RPP products based on 4C (Critical Thinking and Problem Solving, Communication, Collaboration, Creativity and Innovation) obtained "very good" teacher responses with an average score of 3.7.Keywords: Development, Lesson Plans, 4C.